Causes of non-malarial fever in Africa: A systematic review and meta-analysis - Wainaina, Martin; Silva, D.A.V. da; Dohoo, I.; Mayer-Scholl, A.; Roesel, Kristina; Hofreuter, D.; Roesler, U.; Lindahl, Johanna F.; Bett, Bernard K.; Al Dahouk, S. (International Livestock Research Institute, 2022)
Objectives The awareness of non-malarial febrile illnesses (NMFIs) has been on the rise over the last decades. Therefore, we undertook a systematic literature review and meta-analysis of causative agents of non-malarial fevers on the African continent. Materials and methods We searched for literature in African Journals Online, EMBASE, PubMed, Scopus, and Web of Science databases to identify aetiologic agents that had been reported and to determine summary estimates of the proportional morbidity rates (PMr) associated with these pathogens among fever patients. Results A total of 133 studies comprising 391,835 patients from 25 of the 54 African countries were eligible. A wide array of aetiologic agents were described with considerable regional differences among the leading agents. Overall, bacterial pathogens tested from blood samples accounted for the largest proportion. The summary estimates from the meta-analysis were low for most of the agents. This may have resulted from a true low prevalence of the agents, the failure to test for many agents or the low sensitivity of the diagnostic methods applied. Our meta-regression analysis of study and population variables showed that diagnostic methods determined the PMr estimates of typhoidal Salmonella and Dengue virus. An increase in the PMr of Klebsiella spp. infections was observed over time. Furthermore, the status of patients as either inpatient or outpatient predicted the PMr of Klebsiella spp. infections. Conclusion The small number of epidemiological studies and the variety of NMFI agents on the African continent emphasizes the need for harmonized studies with larger sample sizes. In particular, diagnostic procedures for NMFIs should be standardized to facilitate comparability of study results and to improve future meta-analyses. Reliable NMFI burden estimates will inform regional public health strategies.